'Be good, know the rules': Children's perspectives on starting school and self-regulation. (November 2019) - Booth, Ailbhe; O'Farrelly, Christine; Hennessy, Eilis; Doyle, Orla
Despite the importance of self-regulation for school readiness and success across the lifespan, little is known about children's conceptions of this important ability. Using mixed-method interviews, this research examined kindergarten children's (n = 57) perspectives on self-regulation in a disadvantaged area in Dublin, Ireland. Children depicted school as requiring regulation of their emotional, cognitive and behavioural responses. They characterised school as a dynamic setting, placing emphasis on the regulatory challenges of the outdoor environment. Children also described difficulties associated with navigating complex social interactions, often without assistance from external supports. The results inform strategies to support children's emerging self-regulation abilities.